THE EFFECT OF WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES OF PT. SOURCE: ALFARIA TRIJAYA. TBK PEKANBARU BRANCH WITH WORK MOTIVATION AS AN INTERVENING - Wiki Surma Rahayu; Fahmi Oemar; Jeni Wardi (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This study uses this research using a quantitative method and the PLS Structural equational modelling (SEM) statistical test will be used for verifying analysis. The research was conducted at PT Sumber Alfaria Trijaya Tbk Pekanbaru Branch with a total of 57 respondents. The results of the study show that work motivation as an intervening variable has a positive value on the influence of employee work discipline on employee performance at PT Sumber Alfaria Trijaya Tbk Pekanbaru Branch. This means that the work motivation variable as an intervening will strengthen the relationship between the employee work discipline variable and employee performance at PT Sumber Alfaria Trijaya Tbk Pekanbaru Branch, because indeed with good work motivation, it will make employees who initially think that work discipline has no effect on their performance at work to change and realize that no matter how small the mistake they make will have an impact on employee performance and the performance of the company's organization, so high motivation is needed in every employee To always prioritize the interests of the company above personal interests while at work. In order to achieve good employee performance, the leadership of PT Sumber Alfaria Trijaya Tbk Pekanbaru Branch continues to pay attention to improving employee discipline by being more active in supervising, namely supervising the attitudes, behaviors, work passion, morals, attitudes, and work achievements of their subordinates by trying to always be present or present at the workplace so that it is easy to supervise and can provide solutions if there are difficulties faced by employees. The thing that needs to be considered regarding employee performance is that leaders should continue to maintain and increase attention to employees to maintain productivity through emphasis on employees to always be obedient in carrying out work according to the work procedures that have been made.